Aggressiveness in a subtropical shorebird's nest defense is adjusted to the predator species and shared by conspecifics. Issue 5 (8th May 2022) - Brynychová, Kateřina; Sládeček, Martin; Pešková, Lucie; Chajma, Petr; Firlová, Veronika; Elhassan, Esmat; Vozabulová, Eva; Janatová, Veronika; Almuhery, Aisha; Šálek, Miroslav
Abstract: Aggression is an important component of an animal's defense when protecting offspring from predators. Ground nesting birds use a variety of defense strategies. However, their choice according to situation context is poorly known, especially in nonpasserines and in the subtropics and tropics. The ability to distinguish between differently dangerous predator species and the opportunity to share defense with conspecifics are potentially important but little‐studied aspects of nest defense strategy. We experimentally studied the nest defense of Red‐Wattled Lapwing in an individually marked population in a desert area near Dubai, UAE. We used three stuffed models representing 1) a predator dangerous both to adults and to nests (a cat), 2) a nest predator (a raven), and 3) a harmless reference model (a moorhen). We confirmed that the lapwings distinguished between predator species (being most aggressive toward the cat, and least aggressive toward the moorhen) and adjusted their defense strategy accordingly. In addition, conspecific visitors play a variety of roles in parents' defense strategy. They can strengthen the parental reaction, or they can assist in distracting a predator. The visitors included not only nesting neighbors but also nonbreeding floaters. Both parents participated in nest defense to a similar extent, regardless of incubation stage and ambient temperature. This study provides new insight into the complexity of the defensive patterns in ground‐nesting birds inhabiting a hot environment. Comparative experimental research on a range of environments, with various bird species and predator models, can help us to understand the drivers of these defensive behavioral patterns.